Acute Triglyceride Response to 60-Minute Jogging Exercise Among Community-Dwelling Adults in Ternate - Fahmi Rizal; Nikma; Viona Deswitha Khondowa (Jurnal Kesehatan Komunitas Indonesia, 2026)
Background: Elevated triglyceride levels are a recognized modifiable risk factor for cardiovascular disease. While moderate-intensity aerobic exercise is recommended for lipid management, evidence on acute triglyceride responses following 60-Minute jogging session remains limited in Indonesian community settings. Objective: This study aimed to analyze acute changes in blood triglyceride levels following 60-Minute jogging session among community members in Ternate City, Indonesia. Methods: A quantitative pretest–posttest observational design was employed with 50 participants selected via purposive sampling. Triglyceride concentrations were measured using Point-of-Care Testing (POCT) on capillary blood immediately before and after a standardized 60-minute jogging session. Data were analyzed using descriptive statistics and the Wilcoxon Signed-Rank test. Results: Following exercise, the proportion of participants with normal triglyceride levels (<150 mg/dL) increased from 56.0% to 70.0%. The high and very high categories decreased, with the latter reaching 0%. The Wilcoxon Signed-Rank test confirmed a statistically significant reduction in triglyceride levels (Z = −3.421, p < .001) with a large effect size (r = 0.48). Conclusion: A single 60-minute jogging session induces a significant acute improvement in triglyceride profiles. These findings support moderate aerobic activity as an effective, accessible non-pharmacological strategy for cardiovascular risk reduction in community health settings.